Integrating Aesthetic Assessment of Tourism Landscapes into Environment-Based Education Curriculum - Dodi Sukma R.A; Sri Wahyuni (STAI Hubbulwathan Duri, 2025)
Riau Province holds significant potential for the development of natural tourist attractions, particularly around the Koto Panjang Hydropower Reservoir, including Puncak Kompe, Raja Onam, and Taman Bunga Tepian Mahligai. Evaluating the aesthetic quality of these landscapes is crucial for supporting tourism and sustainable development. This study assessed the visual landscape aesthetics of these destinations using the Scenic Beauty Estimation (SBE) method. Data collection involved field observations, photography via DSLR cameras and drones, and questionnaires distributed to two groups of respondents: visitors and non-visitors. The SBE method categorized aesthetic values into low, medium, and high, based on respondent perceptions. The analysis revealed variations in aesthetic quality across the destinations. Puncak Kompe achieved the highest SBE score of 42 among visitors, indicating strong visual appeal. Raja Onam and Taman Bunga Tepian Mahligai also received high aesthetic scores of 49 and 40, respectively, from their respondent groups. Scores above 40 were classified as high, confirming the scenic richness of these locations. These findings highlight the significant aesthetic and visual value of the studied sites, suggesting their potential to attract a broad range of visitors. Additionally, the study illustrates the effectiveness of integrating the SBE method into environmental education. This research offers valuable insights for promoting sustainable tourism development in Riau, while also serving as a reference for incorporating landscape aesthetics into environmental education curricula.